From Crisis to Rise: Indonesia’s Economic Transformation through Four Policy Eras - Hadraji Mufti Abizar Al Ghiffari; Refika Cyntia Sari; M. Fachriansyah (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study investigates Indonesia’s long-term economic transformation across four pivotal eras: the colonial period, the Old Order, the New Order, and the Reformasi era. Employing a descriptive qualitative design with historical analysis, the research elucidates how political transitions, institutional reforms, and global dynamics have interacted to shape the nation's economic architecture. Results indicate that colonial legacies entrenched deep structural inequalities and a dualistic economy, creating a path dependency that continued to influence policy direction after independence. During the Old Order, efforts to assert economic sovereignty were constrained by macroeconomic instability, limited state capacity, and shifting political coalitions. The New Order marked a turning point toward industrialization, macroeconomic stabilization, and openness to foreign investment, generating high growth but also deepening inequality and dependence on external capital. Entering the Reformasi era, decentralization, democratization of governance, and fiscal transparency reshaped institutional frameworks; however, persistent challenges such as regional disparities, productivity gaps, and vulnerability to global shocks remain evident. The study concludes that Indonesia’s economic evolution is non-linear, shaped by historical constraints and gradual institutional adaptation rather than abrupt shifts. Strengthening governance, enhancing domestic industrial competitiveness, and expanding inclusive development policies are essential strategies for supporting long-term resilience. These findings highlight the importance of continuity in policy reform to achieve sustainable growth and to realize the national vision of Indonesia Emas 2045.